2012
DOI: 10.1093/aob/mcs048
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of domestication of yardlong bean, Vigna unguiculata (L.) Walp. ssp. unguiculata cv.-gr. sesquipedalis

Abstract: This is the first report of QTLs for domestication-related traits in yardlong bean. The results provide a foundation for marker-assisted selection of domestication-related QTLs in yardlong bean and enhance understanding of domestication in the genus Vigna.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 25 publications
6
98
2
1
Order By: Relevance
“…The different results likely stem from different crosses being used in these two studies. Similar to the findings of the more recent study [105], four QTLs concentrated in two regions were shown to regulate pod fiber layer thickness, which control pod shattering in cowpea by two genes [49,104]. Pod dehiscence in cowpea may be regulated by a different set of genes.…”
Section: C Shattering In Legumessupporting
confidence: 81%
See 2 more Smart Citations
“…The different results likely stem from different crosses being used in these two studies. Similar to the findings of the more recent study [105], four QTLs concentrated in two regions were shown to regulate pod fiber layer thickness, which control pod shattering in cowpea by two genes [49,104]. Pod dehiscence in cowpea may be regulated by a different set of genes.…”
Section: C Shattering In Legumessupporting
confidence: 81%
“…Genetic analysis of pod shattering has been carried out in various legumes including soybean [48,[93][94][95][96][97][98][99][100][101], common bean [13,44], pea [18,50,102], cowpea [49,[103][104][105][106], lentil [16,46,107], narrow-leaf lupin [47,108], azuki bean [45,109], and common vetch [43,110]. In most of the legumes that have been studied so far, pod shattering is found to be a dominant trait controlled by one or two genes or QTLs (Table 1).…”
Section: C Shattering In Legumesmentioning
confidence: 99%
See 1 more Smart Citation
“…In domesticated species, this is removed or delayed. Breeding experiments have shown singlelocus control of pod dehiscence in lentil (Erskine, 1985), two in mungbean (Isemura et al, 2012), yardlong bean (Kongjaimun et al, 2012) and pea (Weeden, 2007). One locus controls the number of twists along the length of the shattered pod, while the second locus controls the percentage of shattered pods (Weeden and Wolko, 2001;Ambrose and Ellis, 2008).…”
Section: A Genetic Aspects Of Legume Domesticationmentioning
confidence: 99%
“…High genome conservation among species in the genus Vigna has been demonstrated (Fatokun et al, 1992;Somta et al, 2006;Isemura et al, 2007Isemura et al, , 2010Kongjaimun et al, 2012). Mungbean, azuki bean and rice bean belong to the subgenus Ceratotropis which are known as Asian Vigna because they are all originated in Asia.…”
Section: Comparison Of Seed Weight and Days To Flowering Qtls Betweenmentioning
confidence: 99%